COMPARISON OF DIFFERRENT LABORATORY METHODS FOR DIAGNOSIS OF CRYPTOSPORIDIUM - KADIR, MOHAMMED ABDUL AZIZ; ELYASSIN, SUHAIR TARIQ (The Iraqi Journal of Veterinary Medicine, 2021)
The present study was carried on to compare several methods for identification of Cryptosporidium oocysts sp. which conclude modified acid fast stain, Sheather’s flotation solutions, Ritchi formal-ether sedimentation solutions, noval stain and iodine technique. The modified acid-fast stain and its combination with formal – ether technique gave the best demonstration 100%. The most reliable technique for identification of oocysts was formal-ether concentration combination with modified acid fast stain (100%), followed by using modified acid fast stain only (97%), sucrose flotation technique (90%) novel staining technique (85%), formal ether concentration (84%), and iodine technique (69%) respectively.